Cutaneous eyelid melanoma with lacrimal sac metastasis: the potential role of lacrimal fluid as a metastatic pathway. (11th September 2022) - Nakamura, Yoshio; Tanese, Keiji; Kameyama, Kaori; Ota, Yu; Fusumae, Takaiyuki; Hirai, Ikuko; Fukuda, Keitaro; Funakoshi, Takeru
Abstract : Here we present a patient with cutaneous eyelid melanoma patient with lacrimal sac metastasis. Clinicopathological findings in this case support the theory that lacrimal fluid can be a metastatic pathway for tumour cells. Dermatologists should be aware of the possibility that cutaneous eyelid melanoma may involve the nasolacrimal system and should examine it during the perioperative period and in postoperative follow‐up.